Barriers of Intercultural Communication in the Sunni-Shi'a Conflict in Madura - Ferry Adhi Dharma (Kanal: Jurnal Ilmu Komunikasi, 2021)
Until now, the Sunni-Shia conflict in Sampang, Madura has not been fully resolved. Therefore, with a communication science approach, this study will analyze the problems and barriers to intercultural communication that occurs between Sunni and Shia groups, causing eternal conflict. This research was conducted in two places, namely in Karanggayam Village, Omben District, Blu'uran Village, Karang Penang District, Madura, and in Rusunawa Puspa Agro, Sidoarjo. The research method used is the phenomenology of Edmun Husserl. The selection of the phenomenological method was based on the need for research data, namely exploring the experience of intercultural communication of each informant involved in the conflict. The results of the study stated that the barriers to intercultural communication that occur are due to the struggle for social status between Sunni and Shia religious leaders, the low culture of the Madurese community in communicating in the form of firmness in communication, the view of the life of the surrounding community based on syncretism, differences in standards of good or bad values ​​between groups, and perceptions negative relations between groups in the form of prejudice, stereotypes, and ethnocentrism that lead to insincerity in communication. Barriers to Intercultural Communication in the Sunni-Shia conflict in Madura.